The Impact of Firm Size, Leverage, Firm Age, Media Visibility and Profitability on Sustainability Report Disclosure - Maryana, Maryana; Carolina, Yenni (University of Merdeka Malang, 2021)
This study aims to see the impact of firm size, leverage, firm age, media visibility, and industry affiliation on sustainability reporting disclosure as measured by the score of the GRI indicator. This study uses multiple linear regressions with E-views software. This study also utilizes pollution from firms that are admitted to the LQ 45 index listed on the BEI from 2014 to 2018. The research sample used was 18 purposive sampling method selected firms. The results of this study that have been processed simultaneously are that firm size, leverage, firm age, media visibility and profitability have a significant impact on SR disclosure. Partially, Firm Size and Media Visibility do not have a significant impact on SR disclosure. Leverage and Firm Age have a negative and significant impact on SR disclosure, while profitability has a positive and significant impact on SR disclosure.DOI: https://doi.org/10.26905/jkdp.v25i1.4941